2019
DOI: 10.24925/turjaf.v7isp1.154-159.2791
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of Eucheuma sp. (Rhodophyceae) and Laminaria sp. (Phaeophyceae)

Abstract: In this study, antioxidant activities of two macroalgae, Eucheuma sp. J.Agardh and Laminaria sp., J.V.Lamouroux used as food supplements were investigated. The antioxidant activity, free radical scavenging activity, the total content of phenolics, flavonoids and condensed tannins in extracts were determined. The IC50 values of the extracts of Eucheuma sp. and Laminaria sp. on DPPH scavenging activity was 2.26±0.03 mg/g and 2.63±0.03 mg/g of extract, respectively. The maximum total phenolic (5.31±0.04 mg GAE/g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Antioxidant activity in macroalgae is closely associated with the content of total phenolic compounds (Fernando et al, 2018;Ak and Türker, 2019;Arunkumar et al, 2020). It is in accordance with previous studies that phenolic is presently dominantly in macroalga and this compound extracts exhibited a wide range of biological activities, including antiinflammatory activity (Catarino et al, 2017;Neto et al, 2018) and as the most antioxidant potential source (Cox et al, 2010;Machu et al, 2015).…”
Section: Figure 2 Antioxidant Activity Of Ethanol Extract Of E Cottoniisupporting
confidence: 83%
See 1 more Smart Citation
“…Antioxidant activity in macroalgae is closely associated with the content of total phenolic compounds (Fernando et al, 2018;Ak and Türker, 2019;Arunkumar et al, 2020). It is in accordance with previous studies that phenolic is presently dominantly in macroalga and this compound extracts exhibited a wide range of biological activities, including antiinflammatory activity (Catarino et al, 2017;Neto et al, 2018) and as the most antioxidant potential source (Cox et al, 2010;Machu et al, 2015).…”
Section: Figure 2 Antioxidant Activity Of Ethanol Extract Of E Cottoniisupporting
confidence: 83%
“…In addition, this species is able to synthesize significant amount of bioactive compounds which are potential to be developed. Previous studies have reported the valuable constituents of E. cottonii with a wide range of biological activities, such as antidiabetic (Prasasty et al, 2019), antibacterial (Bhuyar et al, 2020;Sukmawati, 2021), antioxidant to protect various diseases and stress (Muawanah et al, 2016;Yanuarti et al, 2017;Wulandari et al, 2018;Bangngalino and Badai, 2018;Sambodo, 2019;Ak and Türker, 2019). Moreover, macroalgae with phlorotannin content have been discovered to possess anti-inflammatory properties (Brown et al, 2014;Sudirman et al, 2018;Gutiérrez-Rodríguez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed a negative correlation between DPPH scavenging activities and both flavonoids and phenolic values. In previous studies, the total phenolic and flavonoid were significantly correlated to IC50 inhibition values, and results show significant negative relationships (Ismail, 2017;Ak and Türker, 2019).…”
Section: Resultsmentioning
confidence: 78%
“…Flavonoids are polyphenolic compounds and are known as safe and non-toxic antioxidants. Seaweeds' phenolic and flavonoid compounds change according to species, environmental conditions, and extraction solvents (Ak and Türker, 2019;Koru et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activity was determined using the DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging method as described by Brand-Williams et al (1995) and Ak and Türker (2018). Different concentrations of methanol-diluted pepper extracts were mixed with DPPH solution after being allowed to stand at room temperature for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%